Diagnosis accuracy of serum glypican-3 level in patients with hepatocellular carcinoma: a systematic review with meta-analysis. Issue 4 (November 2018) - Li, Jian; Wang, Tiezheng; Jin, Boxun; Li, Wenlei; Wang, Zhenshun; Zhang, Haitao; Song, Yunjun; Li, Ning
Background: Previous studies have evaluated the diagnostic value of serum glypican-3 in patients with hepatocellular carcinoma. However, the results remain inconsistent and even controversial. Thus, the aim of the present meta-analysis was to clarify the diagnostic accuracy of serum glypican-3 for hepatocellular carcinoma. Methods: A meta-analysis including 22 studies was performed with 2325 cases and 2280 controls. Relevant studies were searched in the EMBASE, PubMed, and Web of Science databases, covering relevant papers published until November 1, 2017. The quality of the studies was assessed by revised QUADAS tools. Sensitivity, specificity, and other measures were pooled and determined to evaluate the accuracy of serum glypican-3 in the diagnosis of hepatocellular carcinoma by random-effects models. Summary receiver operating characteristic curve (sROC) analysis was performed to summarize the overall test performance. Results: The results showed that the pooled overall diagnostic sensitivity, specificity, and 95% confidence interval (CI) for serum glypican-3 in the diagnosis of hepatocellular carcinoma were 68% (56-79%) and 92% (82-96.0%), respectively. Besides, the summary diagnostic odds ratio and 95% CI for glypican-3 were 23.53 (8.57-64.63). In addition, the area under sROC and 95% CI was 0.87 (0.84-0.90). The major design deficiencies of included studies were differential verification bias, and a lack of clear exclusion and inclusion criteria. Conclusions: The results of this meta-analysis suggested that serum glypican-3 was acceptable as a moderate diagnostic marker in the diagnosis of hepatocellular carcinoma compared with healthy individuals, which could elevate the sensitivity and specificity of diagnosis. Furthermore, more well-designed studies with large sample sizes are needed to show the effectiveness of glypican-3 in the differential diagnosis of hepatocellular carcinoma.